My first book of sign language - Holub, Joan. (New York : Scholastic, 2004)
Pictures of children demonstrate the forming in sign language of alphabetically arranged words, accompanied by illustrations of the words themselves.
"Cartwheel books."
Keywords: Sign language -- Juvenile literature; Finger spelling; Sign language; Alphabet; Deaf; People with disabilities